Thank God you're here: the coming generation and their role in future‐proofing Australia from the challenges of population ageing. Issue 3 (October 2014) - Churchill, Brendan; Denny, Lisa; Jackson, Natalie
Abstract : Like much of the industrialised world, Australia's population is ageing, the implications of which are twofold: increasing demand for publicly funded services and a decline in the supply of prime working‐age people. In grappling with the challenges of a diminishing workforce, the Australian Government is currently relying on its migration programs to provide both the much‐needed labour and skills for the resource boom and also to stimulate the economy through population growth. However, there may be another, not yet fully considered solution to the upcoming demographic problem. This paper investigates how the grandchildren of the baby boomers, termed here the Thank God You're Here generation (Gen TGYH), might impact on Australia's predicted workforce shortage. This generation of workers will enter the labour force as the last of the baby boomers reach retirement age, and will not only be bigger in size than preceding generations (Y, X and Baby Boomers), but also potentially be better educated than the retiring generation. This paper will also canvas the opportunities for both Gen TGYH and employers as well as the challenges for policymakers and governments in maximising the opportunity provided by this generation in the Australian economy.